1990
DOI: 10.1111/j.1471-4159.1990.tb04948.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activities in Relation to pH and Lactate in Postmortem Brain in Alzheimer‐Type and Other Dementias

Abstract: Phosphate-activated glutaminase, glutamic acid decarboxylase, pyruvate dehydrogenase, succinic dehydrogenase, pH, and lactate were measured in frontal cortex and caudate nucleus of postmortem brains from cases of Alzheimer-type dementia (ATD), Down's syndrome, Huntington's disease, and one case of Pick's disease, as well as from sudden death and agonal controls. Lactate levels were higher and pH, phosphate-activated glutaminase, and glutamic acid decarboxylase levels were lower in the agonal controls than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
197
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(211 citation statements)
references
References 23 publications
13
197
0
1
Order By: Relevance
“…Thus, it cannot be assumed that because one particular protein, mRNA, etc is stable, all are stable during a certain PMI. In addition to PMI and storage temperature, other factors such as agonal state at death (Bowen et al, 1976;Butterworth et al, 1983;Harrison et al, 1991;Lewis and Akil, 1997;Perry et al, 1977aPerry et al, , 1982Spokes, 1979;Yates et al, 1990), pH (generally related to agonal state) (Barton et al, 1993;Eastwood and Harrison, 2000;Harrison et al, 1995;Johnston et al, 1997;Kingsbury et al, 1995), freezing time (Roytta et al, 1980), and time or season of death (Bucht et al, 1981;Carlsson et al, 1980; Perry et al, 1977a-d), among many others, have been found to influence the degradationFor levelFof biological products in postmortem brain specimens. Thus, it remains critical to ascertain the post-mortem stability, and the stability under other conditions, of the biological product.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it cannot be assumed that because one particular protein, mRNA, etc is stable, all are stable during a certain PMI. In addition to PMI and storage temperature, other factors such as agonal state at death (Bowen et al, 1976;Butterworth et al, 1983;Harrison et al, 1991;Lewis and Akil, 1997;Perry et al, 1977aPerry et al, , 1982Spokes, 1979;Yates et al, 1990), pH (generally related to agonal state) (Barton et al, 1993;Eastwood and Harrison, 2000;Harrison et al, 1995;Johnston et al, 1997;Kingsbury et al, 1995), freezing time (Roytta et al, 1980), and time or season of death (Bucht et al, 1981;Carlsson et al, 1980; Perry et al, 1977a-d), among many others, have been found to influence the degradationFor levelFof biological products in postmortem brain specimens. Thus, it remains critical to ascertain the post-mortem stability, and the stability under other conditions, of the biological product.…”
Section: Discussionmentioning
confidence: 99%
“…Although enzyme activity measures appear to be affected by brain pH (Perry et al 1982;Yates et al 1990), immunoreactivity of brain proteins and ligand binding to receptors do not appear to differ substantially as a function of brain pH (Harrison et al 1995). However, tissue levels of many species of mRNAs are directly related to brain pH (Harrison et al 1995;Kingsbury et al 1995).…”
Section: Antemortem Factorsmentioning
confidence: 99%
“…However, the severity of agonal state has been reported to be inversely proportional to postmortem brain pH, which appears to be relatively uniform across the brain (Harrison et al 1995). In contrast, brain pH does not appear to change as a function of postmortem interval (Ravid et al 1992;Kingsbury et al 1995).Although enzyme activity measures appear to be affected by brain pH (Perry et al 1982;Yates et al 1990), immunoreactivity of brain proteins and ligand binding to receptors do not appear to differ substantially as a function of brain pH (Harrison et al 1995). However, tissue levels of many species of mRNAs are directly related to brain pH (Harrison et al 1995;Kingsbury et al 1995).…”
mentioning
confidence: 99%
“…Most enzymes are quite stable in autopsy tissue Sims et al 1987;Yates et al 1990;Jiang and Nail 1998;Lovell et al 1998;Wagey et al 1998;Fields et al 1999;Kish et al 1999;Pandey et al 1999;Reiach et al 1999;Zubenko et al 1999;Pappas et al 2000;Kozlovsky et al 2001;Tong et al 2001;Balciuniene et al 2002;Fitzmaurice et al 2002;Irazusta et al 2002). For comparative purposes, an enzyme may be considered to be stable if less than 3% of its activity is lost per hour postmortem, and unstable if 5% or more of its activity is lost per h. By these criteria, a stable enzyme would retain more than 70% of its original activity after 10 h. Results from some published studies are summarized in Table 2.…”
Section: Enzymatic Integritymentioning
confidence: 99%
“…Neither post-mortem interval (PMI) nor time in storage have been shown to significantly affect their integrity, although recoveries from human tissue can be highly variable (for a review see Barton et al 1993). Factors from the ante-mortem period -in particular, the agonal state and the rapidity of death -as well as the method of tissue preparation and storage, may play greater roles in determining post-mortem yields of nucleic acids and proteins (Yates et al 1990;Harrison et al 1991Harrison et al , 1995Kingsbury et al 1995). While it is now generally accepted that PMI may critically affect the preservation of some brain neuropeptides and catecholamines (Dodd et al 1988;Palmer et al 1988a;Arranz et al 1996), many nucleic acids and proteins are remarkably stable post-mortem (Lukiw et al 1990;Yates et al 1990;Harrison et al 1991;Leonard et al 1993;Ludes et al 1993;Johnston et al 1997;Schramm et al 1999;Yasojima et al 2001;Bahn et al 2002).…”
mentioning
confidence: 99%